Emotional Mental Imagery Abnormalities in Monozygotic Twins With, at High-Risk of, and Without Affective Disorders: Present in Affected Twins in Remission but Absent in High-Risk Twins - Di Simplicio, Martina; Lau-Zhu, Alex; Meluken, Iselin; Taylor, Patrick; Kessing, Lars Vedel; Vinberg, Maj; Holmes, Emily Alexandra; Miskowiak, Kamilla Woznica (Frontiers in Psychiatry, 2019)
Background: Mental imagery abnormalities feature across affective disorders including bipolar disorder (BD) and unipolar depression (UD). Maladaptive emotional imagery has been proposed as a maintenance factor for affective symptomatology and a target for mechanism-driven psychological treatment developments. Where imagery abnormalities feature beyond acute affective episodes, further opportunities for innovation arise beyond treatments, such as for tertiary/relapse prevention (e.g., in remitted individuals) or primary prevention (e.g., in non-affected but at-risk individuals). The aim of our study was to investigate for the first time the presence of possible mental imagery abnormalities in affected individuals in remission and at-risk individuals for affective disorders using a familial risk design. Methods: A population-based cohort of monozygotic twins was recruited through linkage between the Danish national registries (N=204). Participants were grouped as: affected (remitted BD/UD; n=115); high-risk (co-twin with history of BD/UD; n=49), or low-risk (no co-twin history of BD/UD; n=40). Twins completed mental imagery measures spanning key subjective domains (spontaneous imagery use and emotional imagery) and cognitive domains (imagery inspection and imagery manipulation). Results: Affected twins in remission reported enhanced emotional mental imagery compared to both low- and high-risk twins. This was characterized by greater impact of (i) intrusive prospective imagery (Impact of Future Events Scale) and (ii) deliberately-generated prospective imagery of negative scenarios (Prospective Imagery Task). There were no significant differences in these key measures between affected BD and UD twins in remission. Additionally, low- and high-risk twins did not significantly differ on these emotional imagery measures. There were also no significant differences between the three groups on non-emotional measures including spontaneous imagery use and cognitive stages of imagery. Conclusions: Abnormalities in emotional prospective imagery are present in monozygotic twins with affective disorders in remission - despite preserved cognitive stages of imagery - but absent in unaffected high-risk twins, and thus do not appear to index familial risk (i.e., unlikely to qualify as “endophenotypes”). Elevated emotional prospective imagery represents a promising treatment/prevention target in affective disorders.